Caring on the Clock : The Complexities and Contradictions of Paid Care Work - Stacey, Clare L. (Clare Louise), 1973-; Armenia, Amy, 1972-; Duffy, Mignon (Book collections on Project MUSE., 2015)
"Caring on the Clock is the first book to bring together cutting-edge research on a wide range of paid care occupations, placing the various studies within a comprehensive and comparative framework. The book includes twenty-two original essays by leading researchers across a range of disciplines--including sociology, psychology, social work, and public health--and provides a wealth of insight into these workers, who take care of our most fundamental needs, often at risk to their own economic and physical well-being"--